ChemInform Abstract: Batch to Flow Deoxygenation Using Visible Light Photoredox Catalysis. Issue 37 (22nd August 2013) - Nguyen, John D.; Reiss, Barbara; Dai, Chunhui; Stephenson, Corey R. J.
Abstract A catalytic one‐pot deoxygenation protocol for primary and secondary alcohols (I) that shows high functional group tolerance is developed.